PENGARUH EKSTRAK SAMBILOTO (Andrographis paniculata Nees.) TERHADAP KUALITAS SPERMATOZOA EPIDIDIMIS Mencit (Mus musculus L.) SWISS WEBSTER - Margaretta, Margaretta; Sumarmin, Ramadhan; Widiana, Rina (STKIP PGRI Sumbar, 2013)
ABSTRACTBitter (Andrographis paniculata Nees.) widely used for the treatment of various diseases, such as influenza, HIV anti-cancer and anti-inflammatory, antifertility. The main content of the bitter is Andrographolide. Andrographolide is the activeantimitotic bitter agentthat prevents cell division (cytokinesis) and reduced sperm count. This study aimed to determine the effect of extract of bitter (Andrographis paniculata Nees.) on the quality of epididymal spermatozoa of mice (Mus musculus L.) Swiss Webster.This research was conducted usingCompletely Randomized Design (CRD) consisting of 4 treatments and 6 replications. Firs (I) treatment was the control, without any bitter extract. Treatments II, III, and IV is the provision of a bitter extract orally for 36 days with a dose of 0.2 g /mice/day, 0.4 g/mice/day or 0.6 g/mice/day. After treatment, the animals were decapitated, dissected and taken epididymal, and then put into the cup petridis already containing PBS solution. Calculation of number of normal and abnormal spermatozoa number were conducted using Improved Neubauer. Data were analyzed by ANOVA (Analysis Of Varian) that epididymal sperm normal and abnormal.The results shoured by the average sperm count is highest in the control of 29.83 x 105, whereas at a dose of 0.2 g of as much as 18.17 x 105, 0.4 g of as much as 24.33 x 105 and 0.6 g as much as 14.17 x 105. Delays due to the reduced number of sperm in the seminiferous tubules of the process of mitosis by antimitotic compounds. While granting that the higher the extract resulted in increased number of abnormal sperm. The causes of abnormal sperm maturation of spermatozoa due to disruption in spermiogenesis phase. The fewer the number of normal sperm treated with increasing doses. It can Â concluded that the extract of bitter given orally for 36 days can decrease sperm quality mice and increases sperm abnormalities.